Productive and profitable black pepper based mixed cropping systems involving tuber crops: Black pepper based mixed cropping systems - Sudha, B; Airina, C K; Yamini Varma, C K; Thankamani, C K; Krishnamurthy, K S; Aravind, Sharon (Journal of Spices and Aromatic Crops, 2023)
An experiment on pepper based mixed cropping systems involving tuber intercrops was carried out at Pepper Research Station (Kerala Agricultural University), Panniyur, Kannur during 2013-14 to 2022-23. Five different black pepper based mixed cropping systems which accommodated five different tropical tuber crops were experimented. The data pertaining to 2020-21, 2021-22 and 2022-23 were separately recorded and the pooled mean worked out for individual crop yields as well as equivalent yields and economics of cultivation of the different systems. The pooled equivalent yield for black pepper + greater yam and black pepper + elephant foot yam mixed cropping systems were recorded in terms of base crop black pepper as 1239.28 and 1214.25 kg ha-1 respectively, significantly superior to all other mixed cropping systems. The equivalent yield recorded for black pepper sole cropping was 561.73 kg ha-1 only. The pooled data revealed higher profitability for black pepper + greater yam mixed cropping system with gross returns, net returns and B:C ratio of Rs. 619637 ha-1, Rs.440043 ha-1 and 3.45 respectively. For black pepper + elephant foot yam system, the respective values were Rs. 607126 ha-1, Rs. 440043 ha-1 and 3.57. The soil properties were also favourably maintained under mixed cropping as that in sole cropping of black pepper as indicated by soil nutrient analysis conducted at the end of the field experiment.